OBTAINING COORDINATION COMPOUNDS OF SALICYLHYDROXAMIC ACID WITH 3D-METAL IONS AND STUDYING THE CRYSTAL STRUCTURE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Salicylic acid is usually a white or light-yellow crystalline powder, slightly soluble in water, and soluble in some organic solvents. Salicylic acid has two main functional groups: